Integration of on-column catalysis and EKC analysis: Investigation of enantioselective sulfoxidations - Füßl, Simone; Trapp, Oliver (Electrophoresis, 2012)
A novel technique is presented to investigate catalytic reactions by coupling a fused-silica capillary coated with an immobilized catalyst and a bare fused-silica capillary to achieve separation of the reaction products and to generate an electroosmotic flow, which drives the transport of the reactants and products through the catalytically active capillary. The principle of this technique is illustrated by the enantioselective sulfoxidation of benzylphenylsulfide with hydrogen peroxide to the corresponding sulfoxide in the presence of a vanadium(IV)-salen catalyst, which is immobilized to nonpolar polysiloxane and permanently bonded to the inner surface of the reaction capillary. The enantiomeric ratio of the reaction product is simultaneously determined by electrokinetic chromatography using 150 mg/mL sulfated β-cyclodextrin as chiral additive in 10 mM sodium dihydrogenphosphate background electrolyte at pH 8.3. In contrast to conventional enantioselective sulfoxidations of benzylphenylsulfide using the vanadium(IV)-salen catalyst, which give ees of up to 11%, an ee of up to 23% was achieved by this approach. Furthermore, the presented technique offers many more advantages, such as improved substrate selectivity using the nonpolar polysiloxane phase as a solvent, the feasibility to perform high-throughput kinetic measurements of substrate libraries, rapid screening and investigation of stereolabile compounds, that is, chiral sulfoxides, and screening of reactions using only minute amounts of reagents.